KOMPOSISI HASIL TANGKAPAN IKAN YANG TERTANGKAP DI SEKITAR RUMPON ATRAKTOR IJUK DI PERAIRAN KABUPATEN NAGAN RAYA PROVINSI ACEH - Hafinuddin, Hafinuddin; Thahir, Muhammad Agam; Yusfiandayani, Roza; Baskoro, Mulyono S; Jaya, Indra (JURNAL PERIKANAN TROPIS, 2019)
The study was conducted to investigate composition of fish catching around palm fiber fish aggregating device (FAD). This research was performed in waters of Nagan Raya District, Indian Ocean on October until December 2018. Palm fiber FAD and coconut fronds FAD was set up at 20-30 m depth. The The research is using survey method and to collecting data, experimental fishing was used to collect data with hand line fishing gear. The results show the types of fish catching in palm fiber FAD is Lepturacanthus savala, Selar crumenopthalmus, Selaroides leptolepis, Rastrelliger kanagurta andÂ  Sardinella lemuru. For coconut fronds FADs, composition of fish catching is Selaroides leptolepis, Rastrelliger kanagurta, Sardenella sirin, Caranx sp, Terapon jarbua, Chorinemus tala dan Upenius mullocensin. Total of fish cacthing in palm fiber FADs is 70 fish. While at coconut fronds FADs is 29 fish. Based on descriptive analysis, the palm fiber FADs is more effective than coconut fronds FADs. This study is very important in the production of fish catching around FADs.